Physics ContributionsA novel method for vaginal cylinder treatment planning: a seamless transition to 3D brachytherapy - Malhotra, Harish K.; Wu, Vincent; Wang, Zhou; Patil, Sachin (Journal of Contemporary Brachytherapy, 2012)
Purpose: Standard treatment plan libraries are often used to ensure a quick turn-around time for vaginal cylinder treatments. Recently there is increasing interest in transitioning from conventional 2D radiograph based brachytherapy to 3D image based brachytherapy, which has resulted in a substantial increase in treatment planning time and decrease in patient through-put. We describe a novel technique that significantly reduces the treatment planning time for CT-based vaginal cylinder brachytherapy. Material and methods: Oncentra MasterPlan TPS allows multiple sets of data points to be classified as applicator points which has been harnessed in this method. The method relies on two hard anchor points: the first dwell position in a catheter and an applicator configuration specific dwell position as the plan origin and a soft anchor point beyond the last active dwell position to define the axis of the catheter. The spatial location of various data points on the applicator’s surface and at 5 mm depth are stored in an Excel file that can easily be transferred into a patient CT data set using window operations and then used for treatment planning. The remainder of the treatment planning process remains unaffected. Results : The treatment plans generated on the Oncentra MasterPlan TPS using this novel method yielded results comparable to those generated on the Plato TPS using a standard treatment plan library in terms of treatment times, dwell weights and dwell times for a given optimization method and normalization points. Less than 2% difference was noticed between the treatment times generated between both systems. Using the above method, the entire planning process, including CT importing, catheter reconstruction, multiple data point definition, optimization and dose prescription, can be completed in ~5-10 minutes. Conclusion: The proposed method allows a smooth and efficient transition to 3D CT based vaginal cylinder brachytherapy planning.